THE UTILISATION OF ICE BREAKING TO INCREASE STUDENT LEARNING ACTIVITIES IN GRADE III OF NURUL ILMI PRIVATE MADRASAH IBTIDAIYAH - Soviana, Vina; Munir, Abdul; Fuaddudin, Fuaddudin (Waniambey: Journal of Islamic Education, 2024)
This research was conducted because of the background of the lack of creativity carried out by the teacher towards efforts to divert the attention of students who are less focused, not too enthusiastic and quickly bored in participating in learning activities, with the aim of this study is to find out the use of Ice Breaking to increase student learning activities in grade III Madrasah Ibtidaiyah Swasta Nurul Ilmi Kota Bima School Year 2024. The type of research used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The location of this research was at Madrasah Ibtidaiyah Swasta Nurul Ilmi Kota Bima. Primary data sources obtained are through the main informants of several teachers at Madrasah Ibtidaiyah Swasta Nurul Ilmi Kota Bima. The results showed that the Ice Breaking method is very effective in solving various problems that occur during the learning process. the use of Ice Breaking is very likely to restore students' enthusiasm in learning. Students no longer feel bored, saturated and depressed during the learning process. Students will feel happy, motivated and have a higher enthusiasm for learning. The use of Ice Breaking can also change the learning atmosphere to be fun. So Ice Breaking is considered important and effective to be used as one of the methods or ways to increase students' learning activities.